(untitled) (Journal of the College of Basic Education, 2022)
There is no doubt that the science of physics has a great contribution in expanding the circle of scientific knowledge among students, as it provides most of the foundations and rules upon which scientific achievements are based, and in this the importance of the relationship between it and other branches of science such as mathematics, chemistry, biology and geology becomes evident, so that it became difficult to define certain limits for it. It deals with the study and research of absolute matter, energy, and their transformations, and the associated natural phenomena that occur in the environment, and such changes that occur to it and the laws that govern it, do not increase the human ability to benefit from knowledge and such simple machines. Photography, means of transportation, and printers are achievements that provide social services